The Political Connection and Tax Aggressiveness Impact to Firm Values of Indonesian Mining Sector 2016-2018 - Sulastri Sulastri; Norma Dwi Kartika Sari (Jurusan Manajemen Fakultas Ekonomi Universitas Negeri Malang, 2021)
This study is conducted to understand the impact of political connection and tax aggressiveness to the firm value, since the previous studies findings are inconclusive. The data used in this study are annual reports from 22 mining sector companies in Indonesia for 2016-2018 period. The data collection method uses secondary data from the Indonesia Stock Exchange website (www.idx.com). After analyze by multiple linear regression technique, the results show that tax aggressiveness has an effect on firm value. However, political connections have no effect on company value. Therefore, it is clear that political connection is less crucial in determining firm value, especially for mining industries in Indonesia because they are already well-established and less competitive. However, tax aggressiveness can be considered as a factor in influencing firm value in mining industries